PENANGANAN TRAUMA DENGAN KONSELING KREATIF PSIKODRAMA - Octaviano, Arista (Universitas Palangka Raya, 2023)
In everyday life, humans are required to comply with the norms and rules that apply in the surrounding environment. In this case, of course humans need the help of other people, especially when they have a history of trauma. This assistance can be in the form of creative counseling with psychodrama techniques. This article, which was compiled using the systematic literature review technique, discusses the causes of trauma, counseling strategies using psychodrama techniques, and the effectiveness of counseling using psychodrama techniques. The primary data in this article were obtained through a literature study of related articles. As a result, trauma can be caused by unwanted events that attack an individual's psyche. In handling it through psychodrama technical counseling, individuals are assisted to explore their feelings of anxiety. This counseling has not proven to be effective in overcoming trauma, but it can help clients feel better and be able to deal with their trauma triggers.